Functional quantification of oral motor cortex at rest and during tasks using activity phase ratio: A zero-setting vector functional near-infrared spectroscopy study - Arai, Masaaki; Kato, Hikaru; Kato, Toshinori (Frontiers in Physiology, 2022)
It has been suggested that oral frailty associated with oral hypokinesia may cause dementia. However, a method for identifying and detecting activation of the oral motor cortex (OMC) from above the scalp has not yet been established. Functional near-infrared spectroscopy (fNIRS) is useful for studying the brain function of oral movement because it can measure subjects in a sitting position with almost no restrictions. This study attempted to detect OMC activation using fNIRS as an indicator of initial dips (0 < [deoxyhemoglobin (ΔDeoxyHb)] or 0 < [(ΔDeoxyHb-oxyhemoglobin (ΔOxyHb))/√2]) to detect local brain activity accurately. The analysis method using active phase ratio (APR) as the new functional index is a technology that can quantify brain function in real time without being affected by motion artifacts such as the temporalis muscle. Fourteen healthy participants performed a unilateral bite task for 3 seconds 10 times while sitting. We measured via 46 channels the concentration changes in ΔOxyHb and ΔDeoxyHb, including the OMC area estimated from three-dimensional magnetic resonance imaging measurements, of 40 subjects during the task. In the vector analysis, the probability of initial dips (i.e., APR) in 140 trials was calculated using the average changes in ΔDeoxyHb and ΔOxyHb. The significant regions (z-score ≥ 2.0) of APR and ΔOxyHb in the task were compared. As per anatomical magnetic resonance imaging, APR of the statistically significant bilateral sites was within the estimated OMC area (56–84 mm outside of and 4–20 mm ahead of Cz) ; further, ΔOxyHb increased beyond the OMC areas and only on the bite side. The increases in APR relative to resting during the right bite task were 27.9% (right OMC) and 17.9% (left OMC). The increases in APR during the left bite were also bilateral. The bite task APR significantly increased within the estimated OMC area in the right and left brain. Compared to ΔOxyHb, APR can detect bilateral brain activity confined to the estimated OMC region and is excellent at detecting and quantifying OMC brain activity temporally and spatially. It was suggested that brain function mapping of ΔOxyHb alone may be misleading to brain activity in oral movement.